Peran Guru PPKn, Partisipasi Pol Peran guru ppkn dalam menumbuhkan partisipasi politik pemilih pemula di man 1 pontianak - Pamilu, Suryo; Achmadi; Atmaja, Thomy Sastra (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
The purpose of this study was to determine the influence of PPKn teachers in encouraging political involvement of students as first-time voters. The researchers used qualitative research techniques that include a descriptive approach. Data collection methods include interviews, observations, literature reviews, and documentation. The data analysis approach consists of three steps: data reduction, data presentation, and inference. Credibility tests are used to assess the veracity of the data. The research findings revealed that: (1) the role of PPKn teachers in fostering student political participation as beginner voters through learning activities in MAN 1 Pontianak was carried out through the learning implementation plan (RPP), the implementation of PPKn learning, and evaluation of learning outcomes. (2) PPKn teachers play a role in fostering political participation of students as beginner voters outside the classroom by organizing election activities for Class Leaders, Study Group leaders, and student council leaders in MAN 1 Pontianak. In practice, the student council president is elected by majority vote, as well as the class president, and the head of the study group is elected by agreement.